2018
DOI: 10.1101/286468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unmodified, autologous adipose-derived regenerative cells improve cardiac function, structure and revascularization in a porcine model of chronic myocardial infarction

Abstract: Numerous studies have investigated cell-based therapies for myocardial infarction (MI), with mixed results. In the present study the left anterior descending (LAD) artery of pigs was occluded for 180 min. Four weeks later, the mean left ventricular ejection fraction (LVEF) was shown to have been reduced to approximately 35%. At that time, 18×106 unmodified, autologous adipose-derived regenerative cells (UA-ADRCs) were delivered into the LAD vein (control: delivery of saline). Six weeks following UA-ADRCs/salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…A study on fresh, uncultured cells that were isolated from adipose tissue of pigs using the Transpose RT system and Matrase Reagent showed that approximately 40% of cells in the stromal vascular fraction were immunopositive for CD29 (thereafter: CD29 + ) and CD44 + [95], which are markers of adipose tissue-derived stem cells[50,96]. Furthermore, on average only 9% of the cells were CD45 + (a marker of blood derived cells[50]), and on average only 11% of the cells were CD31 + (a marker of endothelial cells[50]).…”
Section: Discussionmentioning
confidence: 99%
“…A study on fresh, uncultured cells that were isolated from adipose tissue of pigs using the Transpose RT system and Matrase Reagent showed that approximately 40% of cells in the stromal vascular fraction were immunopositive for CD29 (thereafter: CD29 + ) and CD44 + [95], which are markers of adipose tissue-derived stem cells[50,96]. Furthermore, on average only 9% of the cells were CD45 + (a marker of blood derived cells[50]), and on average only 11% of the cells were CD31 + (a marker of endothelial cells[50]).…”
Section: Discussionmentioning
confidence: 99%
“…Haenel et al, 2018). Specifically, ADRCs that were isolated with the Matrase enzymatic reagent and the Transpose RT system may contain approximately 40% of cells that are immunopositive for CD29 and CD44, which are markers of ASCs (Haenel et al, 2018). These authors also reported a colony forming units (CFU) frequency (considered to be an indicator of stemness) of approximately 11% of ADRCs isolated with the Matrase enzymatic reagent and the Transpose RT system.…”
Section: Differences In the Effectiveness Of Various Systems And Methmentioning
confidence: 98%
“…Isolating ADRCs with the Matrase enzymatic reagent and the Transpose RT system (InGeneron) appears advantagous to other commercial cell separation systems (c.f. Haenel et al, 2018). Specifically, ADRCs that were isolated with the Matrase enzymatic reagent and the Transpose RT system may contain approximately 40% of cells that are immunopositive for CD29 and CD44, which are markers of ASCs (Haenel et al, 2018).…”
Section: Differences In the Effectiveness Of Various Systems And Methmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative, previously unpublished example how autologous, adipose derived stem cells can stay locally, survive and engraft in the new host tissue into which the cells were applied, differentiate under guidance of the new microenvironment, integrate into the new host tissue and participate in building new vascular structures in the host tissue. The panels show photomicrographs of paraffin-embedded, 5 µm thick tissue sections of a post mortem heart from a pig, taken from the left ventricular border zone of myocardial infarction ten weeks after experimental occlusion of the left anterior descending (LAD) artery for three hours, followed by delivery of eGFP-labeled autologous ASCs into the balloon-blocked LAD vein (matching the initial LAD occlusion site) at four weeks after occlusion of the LAD (experiments are described in detail in [111]). (a-e) One tissue section was stained with DAPI (blue) (a) and processed for immunofluorescent detection of GFP (green) (b), von Willebrand factor (vWF) (red) (c) and Troponin (yellow) (d).…”
Section: Statement #8: a Certain Challenge In Research With Ua-adrcs mentioning
confidence: 99%